Older patients are more likely to breach the 4-hour target in Scotland. Issue 12 (1st June 2020) - Quinn, Jonathan; Buchanan, Scott; Myint, Phyo Kyaw; Ellis, Graham
Abstract : Objective: To determine if age is a factor in a patients' likelihood of breaching the 4 hour time target to admission/discharge in emergency departments (EDs) within NHS Scotland. Methods: We used data from the Information Service Division Scotland to analyse all ED attendances in Scotland between January 2015 and September 2018 (n=5 596 642). We assessed the likelihood of time to admission/discharge being within 4 hours, 8 hours and 12 hours for all age categories (reference category 20 to 24 years). Univariable logistic regressions were carried out for sex, Scottish Index of Multiple Deprivation level and both major (potentially life threatening) and minor (not immediately life threatening) incidences. Results: The likelihood of breaching the 4-hour target increased linearly with age from 15 to 19 years upward. Patients ≥85 years were significantly (p<0.001) more likely to have breached than patients aged 20 to 24 years (OR 3.80, 95% CI: 3.73 to 3.86). When considering major incidents, patients aged ≥85 years were more likely to have breached than those aged 20 to 24 years (OR 2.05, 95% CI: 2.01 to 2.09, p<0.001). The same was true of minor incidents (OR 2.85, 95% CI: 2.73 to 2.98, p<0.001). Conclusions: Older age is associated with a higher probability of breaching waiting time targets in a linear fashion within NHS Scotland, which is consistent with previous single hospital or regional studies. This association may be due to the higher proportion of elderly patients being admitted or a more systemic issue, but regardless, the elderly are being put more at risk.